Estudo crítico das propriedades do OPAC 2.0: uma proposta de metodologia de análise - Rafael Goncalves Dias (2018)
In the interactive context of Web 2.0, Online Public Access Catalogs (OPAC) have undergone transformations associated with new user behaviors and demands. Technologies coming from Web 2.0 have been increasingly used by services available on the Internet, such as in catalogs of media (YouTube, Spotify), commercial catalogs (Amazon, American), social networks, blogs and, in some cases, bibliographic catalogs. Attention was drawn to the lack of evidence and evaluation methods for exploiting the benefits of Web 2.0 in catalogs, especially bibliographic ones. According to the reviewed literature, there are assumptions that the discrepancy between library catalogs and the others, could discourage the users in the use of this instrument. Thus, the objective of this research is to develop a method of analysis that allows to clarify the level of alignment of the OPAC regarding the concepts, principles and resources of Web 2.0. In this sense, the properties of Web 2.0 and catalogs were revised in order to develop the proposed model with theoretical basis. The Model of Analysis of Catalog 2.0. (MAC 2.0) was developed and validated through a case study with eight catalogs divided into two categories: the bibliographical ones (Pergamum-UFMG, SophiA-BN, OMNIS-PUCRS and WorldCat-OCLC) and the non-bibliographic (Americanas, Amazon, YouTube and Spotify). The MAC 2.0 proved to be efficient in analyzing any kind of catalog regarding the essentials of Web 2.0. Through it was possible to confirm the assumption that non-bibliographic catalogs are more developed, however, there was no great discrepancy. It was concluded that the bibliographic OPACs analyzed, and probably any other type that is available via the web, are already within the concept Web 2.0 because it meets the principles and offer several resources of this environment, however it has been noticed that the libraries OPAC need of such efficient methods of engaging users to interact with the service and resources made available